MEDICATION ADHERENCE AND MENTAL HEALTH AMONG PATIENTS WITH SCHIZOPHRENIA AT LOA BAKUNG PRIMARY HEALTH CENTER, SAMARINDA - Najdah; Rusni Masnina; Ni Wayan Wiwin Asthiningsih; La Debi Atthoba (PRIMA WIYATA HEALTH, 2026)
Background: Schizophrenia is a chronic severe mental disorder associated with impaired functioning and high relapse rates. Medication nonadherence remains a major challenge in maintaining mental health stability, particularly in primary health care settings where resources are limited. Objectives: To examine the association between medication adherence and mental health status among outpatients with schizophrenia at Puskesmas Loa Bakung Samarinda. Methods: A cross-sectional analytic study was conducted from October to November 2024 involving 40 outpatients with schizophrenia selected through total sampling. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8), while mental health status was measured using the General Health Questionnaire-12 (GHQ-12). Data were analyzed using descriptive statistics and the Chi-square test with a significance level of 0.05. Results: Most participants had low medication adherence (57.5%) and experienced mild psychological distress (47.5%). Bivariate analysis showed a statistically significant association between medication adherence and mental health status (p < 0.001), with patients who had moderate to high adherence showing a lower likelihood of psychological distress (OR = 0.032; 95% CI: 0.003–0.295). Conclusion: Medication adherence was significantly associated with mental health status among outpatients with schizophrenia in a primary health care setting. These findings indicate an important relationship between adherence and psychological condition, although causal conclusions cannot be drawn due to the cross-sectional design.